Uji Sahih Observasi Hilal Siang Hari dengan Hisab Hakiki Kontemporer Sistem Ephemeris Al-Falakiyah - Isroqunnajah Isroqunnajah; M Hadi Masruri; Muhammad Syamsu Alam Darajat (University of Muhammadiyah Sumatera Utara, 2022)
In Indonesia, there are many experts in astronomy, one of which is Sriyatin Shodiq Al-Falaky with his scientific work Ephemeris Al-Falakiyah. This research method uses a qualitative descriptive approach and the type of research is a field study. The research source is the calculation of the beginning of the month of Ramadan and Shawwal with the Ephemeris-Al-Falakiyah system and astrophotography as the primary source. The secondary source is the calculation of the beginning of the month of Ramadan and Shawwal from various reckoning systems in Indonesia. Data collection was carried out by interviewing the main character Sriyatin Shodiq Al-Falaky. The results of the study found that the Ephemeris Al-Falakiyah system of scientific work by Sriyatin Shodiq Al-Falaky used the contemporary essential method of reckoning. The results of the calculation of the beginning of Ramadan and Shawwal as the determinants of the beginning of the Hijri month are very accurate and can be compared with various reckoning systems in Indonesia and there are no significant differences with other contemporary methods of reckoning.